Effect of water addition on freezing point and components of raw milk from Jersey and Holstein cows (UNED Research Journal, 2019)
Introduction: The freezing point is used to assess the quality of raw whole milk and its byproducts. Objective: To determine the effect of water addition on freezing point, bromatological composition, urea content, somatic cell content and bacterial content in raw milk. Methods: During the first stage, we took 35 samples of milk (80mL) from the towns of Turrialba in Cartago, and Zarcero in Alajuela (April and October 2018). We added water (5, 10, 15, 20, 25, and 30% w/w) and kept an unadulterated sample as control (five repetitions each). Results: The addition of 5% water (w/w) was enough to alter all parameters. On a second stage, we tested lower concentrations (1, 2, 3, 4, and 5% w/w). Conclusion: The addition of 1% water (w/w) produced significant changes only on three parameters: freezing point, bromatological contents, and somatic cell count.
Keywords: milk protein; milk solids; water adulterations; milk urea nitrogen; milk lactose; milk fat